Respuesta :

Answer:

B and D

Step-by-step explanation:

Given

2a² + 8a - 15 = 3a - 3 ( subtract 3a - 3 from both sides )

2a² + 5a - 12 = 0 ← in standard form

To factorise the quadratic

Consider the factors of the product of the a² term and the constant term which sum to give the coefficient of the a term, that is

product = 2 × - 12 = - 24 and sum = + 5

The factors are + 8 and - 3

Use these factors to split the a- term

2a² + 8a - 3a - 12 = 0 ( factor the first/second and the third/fourth terms )

2a(a + 4) - 3(a + 4) = 0 ← factor out (a + 4) from each term

(a + 4)(2a - 3) = 0 ← in factored form